CCL26/eotaxin‐3 is more effective to induce the migration of eosinophils of asthmatics than CCL11/eotaxin‐1 and CCL24/eotaxin‐2. Issue 2 (26th March 2013) - Provost, Véronique; Larose, Marie‐Chantal; Langlois, Anick; Rola‐Pleszczynski, Marek; Flamand, Nicolas; Laviolette, Michel
Abstract : CCL26 induced a biphasic migration of asthmatic eosinophils, with the later phase uninhibited by CCR3 blockade. Abstract : CCL11, CCL24, and CCL26 are chemokines involved in the recruitment of eosinophils into tissues and mainly activate CCR3. Whereas the genomic or pharmacological inhibition of CCR3 prevents the development of experimental asthma in rodents, it only impairs the recruitment of eosinophils by ∼40% in humans. As humans, but not rodents, express CCL26, we investigated the impact of CCL11, CCL24, and CCL26 on human eosinophils recruitment and evaluated the involvement of CCR3. The migration of eosinophils of healthy volunteers was similar for the three eotaxins. Eosinophils of mild asthmatics had a greater response to CCL11 and a much greater response to CCL26. Whereas all eotaxins induced the migration of eosinophil of asthmatics from 0 to 6 h, CCL26 triggered a second phase of migration between 12 and 18 h. Given that the CCR3 antagonists SB 328437 and SB 297006 inhibited the 5‐oxo‐eicosatetraenoate‐induced migration of eosinophils and that the CCR3 antagonist UCB 35625 was not specific for CCR3, CCR3 blockade was performed with the CCR3 mAb. This antibody completely blocked the effect of all eotaxins on eosinophils of healthy subjects and the effect of CCL24 on the eosinophils of asthmatics. Interestingly, CCR3 blockade did not affect the second migration phase induced by CCL26 on eosinophils of asthmatics. In conclusion, CCL26 is a more effective chemoattractant than CCL11 and CCL24 for eosinophils of asthmatics. The mechanism of this greater efficiency is not yet defined. However, these results suggest that CCL26 may play a unique and important role in the recruitment of eosinophils in persistent asthma.